The Principal Trends of the Development of Radiological, Chemical and Biological Detection Equipment of Foreign Сountries - N. B. Lopatina; D. V. Frolov (Вестник войск РХБ защиты)
The lecture is intended for the improvement of the professional skills and knowledge of the students and graduates of military schools in the field of foreign chemical, biological and radiological detection equipment. Three problems are considered in the lecture: 1) the principal trends of the development of radiological detection equipment of foreign countries; 2) the principal trends of the development of chemical detection equipment of foreign countries; 3) the principal trends of the development of biological detection equipment of foreign countries. It is shown in the artice, that all the research and development in the field of radiological, chemical and biological reconnaissance tools are aimed at broad unification and miniaturization of the devices. They are also aimed at the creation of new and modernization of existing means of detection and identification of radioactive and toxic substances and biological pathogens.